Mosaic trisomy 8 detected by fibroblasts cultured of skin - Giraldo Ospina, Gustavo Adolfo; Gómez Camacho, Ana Milena; Mora Barreto, Lina Maria; Suarez Obando, Fernando; Moreno Niño, Olga María (Colombia Medica, 2016)
Introduction: Mosaic trisomy 8 or "Warkany’s Syndrome" is a chromosomopathy with an estimated prevalance of 1:25,000 to 1:50,000, whose clinical presentation has a wide phenotypic variability. Case Description: Patient aged 14 years old with antecedents of global retardation of development, moderate cognitive deficit and hypothyroidism of possible congenital origin. Clinical Findings: Physical examination revealed palpebral ptosis, small corneas and corectopia, hypoplasia of the upper maxilla and prognathism, dental crowding, high-arched palate, anomalies of the extremities such as digitalization of the thumbs, clinodactyly and bilateral shortening of the fifth finger, shortening of the right femur, columnar deviation and linear brown blotches that followed Blaschko’s lines. Cerebral nuclear magnetic resonance revealed type 1 Chiari’s malformation and ventriculomegaly. Although the karyotype was normal in peripheral blood (46,XY), based on the finding of cutaneous mosaicism the lesions were biopsied and cytogenetic analysis demonstrated mosaic trisomy 8: mos 47,XY,+8[7]/46,XY[93]. Clinical Relevance: Trisomy 8 is clinically presented as a mosaic, universal cases being unfailingly lethal. In this particular case, cutaneous lesions identified the mosaic in tissue, although the karyotype was normal in peripheral blood. The cutaneous mosaicism represented by brown linear blotches which follow Blaschko’s lines is a clinical finding that has not previously been described in Warkany’s syndrome.